Provision of Physical Therapy at a Long-Term Acute Care Hospital for Patients Awaiting Lung Transplantation: A Case Report With 3 Participants. Issue 4 (October 2016) - Thrush, Aaron; Skrzat, Julie
Abstract : Introduction: Although the number of individuals awaiting lung transplantation is increasing, little is known about the impact of physical therapy (PT), particularly among candidates who require prolonged hospitalization and high levels of supplemental oxygen. This article describes the provision and outcomes of PT for 3 lung transplant candidates at a long-term acute care hospital (LTACH). Case Presentation: Each patient was admitted to a hospital with exacerbation of lung disease and, after being medically stabilized and listed for transplant, transferred to our LTACH for continued medical care of his tenuous medical state. Patients participated in PT to maintain their function and remain candidates for transplant, and to promote improved outcomes after transplant. Length of stay varied from 21 to 107 days. Results: All patients made clinically important improvements in Six-Minute Walk Test distance. Physical therapy was scheduled 5 times per week and was completed 95% of the time. Conclusions: All 3 patients made significant gains despite end-stage disease and exceptionally low pulmonary reserve, and were able to participate in daily PT during prolonged hospitalizations. The results demonstrate the potential for favorable functional improvements in a subset of people with more severe disease and more critical ongoing medical needs than previously described in the literature.